Estudo da diversidade de Hymenoptera parasitoides como fator de integração da universidade com a educação básica em São Carlos, SP - Victorino Ibelli, Bárbara (2022)
More than half of all invertebrates described are insects, and among these, Hymenoptera appears with about 10,500 species in Brazil. The great diversity of this order shows that its individuals have important functions, such as pollination and population control, factors of relevance in the ecological relationships of these animals. Parasitoids can be used as indicators of the degree of preservation, of anthropogenic actions, and also in studies to estimate the richness of species found in certain regions. The Ichneumonoidea superfamily includes 27% of the known Neotropical Hymenoptera genera, however, it appears to be the least known superfamily in the tropics among other parasitoid wasps. Urban ecosystems are expanding and urbanization is a major driver of biodiversity loss. There are few surveys of the fauna of parasitoid wasps, especially of the Ichneumonoidea in urban areas. Environmental education can be a transformative tool to raise awareness in society about the evils that affect the environment. In this sense, the involvement of basic education schools in the awareness and real identification of environmental problems by basic education students, gives them the opportunity to very early, sensitized, contribute to a critical and emancipatory environmental awareness. This study aimed to survey the diversity of the fauna of parasitoid insects in an urban area of the city of São Carlos, SP; using the school environment and the school-university approach as a collection area through the “Junior Scientific Initiation” tool. For this, eight schools in the urban perimeter of the city of São Carlos, SP, were used, in which Malaise traps were inserted to collect Hymenoptera parasitoids. The results made it possible to bring information about the ecological importance of Hymenoptera parasitoids to the school community, demonstrating the importance of participation in Junior Scientific Initiation within the research. In the faunal survey of Ichneumonoidea in an urban area, there were the first citations in Brazil for Lissonota pseudeleboea Ugalde & Gauld, 2002 and Syzeuctus sp. close to S. vedoris Ugalde & Gauld, 2002 (Hymenoptera, Ichneumonidae, Banchinae) and a new species of Zonopimpla Ashmead (Hymenoptera, Ichneumonidae, Pimplinae). The direct contact of the university with the school environment allowed an approach with positive results, opening new possibilities for future partnerships.